The Effect of Using Flashcard Improving Students Speaking Achievement Through Drilling Technique - Resty Wahyuni; Nindi Vourezky (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2021)
This research deals with classroom action research which is mainly aimedtoimprovethe students speaking achievement through implementing drilling technique assisted by media flashcard,itwas conductedatVII-3 grade classintocycles activities. The data were classified into quantitative data and qualitative datainwhich collected through observation sheet, interview, diary note, speaking test.The criteria of ability was 70 which based on minimum ability criterion (KKM) of SMP Swasta Bandung. Basedonthe speaking test the mean score ofpre-testwas28.3,infirstcycletestthemeanofscorewas 66.6 and the second cycle test the mean of score was 83. The improvement also can be seen from the percentage of the students speaking achievement, in pre-test was 0% students can get point more than 70. In first cycle test was 53.4% students get point more than 70. In second cycle test 100% students got point more than 70, it means that teaching by using drilling technique can help students to improve them in speaking achievement. This technique also make the students feel enjoy, comfortable, and more creative to create the ideas without worrying make mistakes through media flashcard.